(untitled) (Global Journal of Human-Social Science, 2011)
The study focus on the living conditions of respondents in the study area determine their poverty level and examine the existence of income inequality among farmers in the study area A multistage random sampling was used to select the 150 respondents from the two Local Governments Areas a well structured questionnaire was used to collect primary data from the farmers Data collected was analysed using descriptive statistics Gini coefficient and FGT poverty ratio Majority of the farmers are male and the mean age for food crop livestock and mixed farmers are 51years 50years and 49 years respectively Household size of 5 members or less is generally above average in the study area Livestock farmers accounted for the highest value respondents without formal education i e 32 5 percent most of the farmers are educated While personal savings and cooperative sociteis are the major source of fund for agricultural production in the study area commercial banks are least patronized for funding in the 3 categories of farm practices Result of the living condition of the respondents reveals that 58 3 percent of the mixed farmers lived in family house while 20 percent of livestock farmers lived in their personal apartment While 62 percent of crop farmers uses pit latrine for faecal disposal 13 3 percent of mixed farmers used water closet Majority of the respondents sourced their water from dug well only 1 7 percent of those engaged in mixed farming sourced water from government provision of pipe borne water The result showed that the moderate poverty line are 1 222 86 1566 45 and 1381 26 for food crop farmers livestock farmers and farmers that engage in mixed farming respectively while the core poor are 611 43 783 22 and 690 63 for the three group of farmers